Characterization of air pollution in pre-covid 19 time using the IVE model applied to mobile sources in urban areas - Cuba Cornejo, Carmen Luz (2021)
In this article we present the design of effective control strategies (IVE Model), to predict atmospheric pollutants, greenhouse gases and toxins, from mobile sources, made up of 800 motorized vehicles, obtained from the records of the transport office of the Provincial Municipality of Ica. through an inventory of emissions from mobile sources, emission factors, activity and distribution of the vehicle fleet. The results obtained are Carbon Monoxide (CO, 23235.23 t/year), Volatile Organic Compounds (VOC: 12123.55 t / year), Nitrogen Oxides (Nox: 361.76 t/year), Evaporative Volatile Organic Compounds (COVevap: 455.2 t / year), Particulate Material (PM: 361.76 t / year) and Sulfur Oxides (Sox: 50.75 t / year). Where the highest CO emissions are cars and motorcycles, representing 45.72% and 36% of the total CO emissions released in the study area. It is concluded that prevention measures and actions such as transport management, control of vehicular emissions, promotion of the use of clean fuels, as a way of mitigating the atmospheric pollutants that could be generated, be established.